The Protocol of the Gods: A Study of the Kasuga Cult in Japanese History - Watson, Michael G (Japanese religions, 1995)
Review of Grapard, Allan G. The Protocol of the Gods: A Study of the Kasuga Cult in Japanese History. Publisher: Berkeley : Univ of California Pr, 1992